The impact of ChatGPT on higher education : exploring the AI revolution - Kurban, Caroline Fell; Sahin, Muhammed; Mitchell, Ted (Emerald Publishing Limited, 2024)
In an ever-evolving educational landscape, traditional methods face unprecedented challenges. The Impact of ChatGPT on Higher Education takes you on a trailblazing journey into ChatGPT's transformative potential and the ethical considerations in higher education. Authored by experts at the forefront of educational transformation and technology's impact on learning, this book offers invaluable insights for educators, leaders, policymakers, and AI enthusiasts. Dive deep with the authors as they navigate from theory to practice, unravelling power dynamics, social structures, and ChatGPT's profound influence. Real-world examples and a captivating case study from MEF University provide tangible evidence of ChatGPT's impact on education. Explore how ChatGPT raises critical questions about course planning, assessments, teaching, and AI's role in education. The authors illuminate issues related to academic honesty, ethics, bias, misinformation, cost, equity, and data privacy. As AI technologies continue to evolve and impact education, The Impact of ChatGPT on Higher Education provides valuable guidance and insights for educators and researchers seeking to harness the power of ChatGPT in their work.